Approaches to the Assessment Liabilities’Analysis - T. V. Pashchenko; N. N. Shakirova (Учёт. Анализ. Аудит, 2023)
The paper substantiates the approach to the assessment liabilities as an independent object of analysis. The research theme is relevant from several positions: the formation trend of estimated liabilities is gaining wide popularity; their creation is dictated by new trends in the macro-environment; stakeholders’ requirements; transforming legislation in accounting and reporting; the competitive environment for the functioning of an economic entity. The purpose of the study is to develop recommendations for expanding the classification of assessment liabilities and determining the sequence of their analysis as a special object. This affects the assessment of financial indicators and management decisions, as well as adjusting comprehensive analytical coefficients, considering the specifics of the formation of estimated liabilities. The work is based on the researching and generalization of theoretical materials on the development and formation of financial statements, methods for a comprehensive analysis of organizations’ activities. In substantiating the principles for calculating indicators and approbating the results, the authors used the actual reporting data of several largest Russian enterprises. They applied such research methods as monographic, data systematization and its analysis. Author’s working-out and proposals can be useful both for scientists and methodologists as a basis for continuing scientific research and analysis of the organization’s activities, and for specialists in preparing financial statements, for making managerial decisions and changing accounting policies (to justify a change in the procedure for assessing estimated liabilities).